2013
DOI: 10.1098/rspa.2012.0458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminium on hydrogen-induced fracture behaviour in austenitic Fe–Mn–C steel

Abstract: It is known empirically that the addition of aluminium as a solute in high-Mn austenitic steels dramatically improves their resistance to hydrogen-induced embrittlement. A variety of experimental techniques, including the characterization of trapping sites and high-resolution observation of fracture facets, have been used to reveal the mechanism by which aluminium induces this effect. It is found that transgranular fracture is promoted by the segregation of hydrogen to mechanical twin interfaces and to any -ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 32 publications
(46 reference statements)
2
42
1
Order By: Relevance
“…[37] A similar effect has been observed in high-manganese austenitic steels, where the effect of aluminum on the stacking fault energy increases the resistance to hydrogen embrittlement by reducing the tendency to form twin-boundary sites susceptible to embrittlement. [22] The high volume fraction of austenite can be expected to increase the resistance to hydrogen embrittlement by introducing trapping sites either in the austenite, or in the form of the large area of interface between the fine bainite plates and thin films of austenite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] A similar effect has been observed in high-manganese austenitic steels, where the effect of aluminum on the stacking fault energy increases the resistance to hydrogen embrittlement by reducing the tendency to form twin-boundary sites susceptible to embrittlement. [22] The high volume fraction of austenite can be expected to increase the resistance to hydrogen embrittlement by introducing trapping sites either in the austenite, or in the form of the large area of interface between the fine bainite plates and thin films of austenite.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] The large fractions of austenite possible in these steels allow improvement in mechanical properties by transformation-induced plasticity, [21] and the presence of austenite is known to result in increased trapping of hydrogen. [7,22] The diffusion of hydrogen at 300 K (27°C) is also much slower (2 9 10 8 times) in austenite than in ferrite. [1,23] The percolating austenite structure has been observed to slow diffusion, [24] and the effective diffusivity of ferrite is also reduced by the large number of defects present.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated a role for e9-martensite, which is recognised to be sensitive to hydrogen-induced fracture. However, the e9-martensite was reported to form during deformation at lower temperatures in Fe-0?6C-17Mn alloy, 13 at decarburised layers in Fe-0?6C-15Mn-2Cr alloy 14 or following in situ hydrogen charging of Fe-0?6C-18Mn, 15 none of which is related directly to the static fracture condition.…”
Section: Deformation-induced Transformationmentioning
confidence: 99%
“…In the study of Ryu et al (2013), the transformation of ɛ-martensite contributed to hydrogen embrittlement, and was attributed to the reduced SFE by hydrogen. In contrast, in this study of the effect of hydrogen content on hydrogen embrittlement in TWIP steels, hydrogen embrittlement occurred without the transformation of ɛ-martensite and without hydrogen affecting the strain hardening behaviour of the steel, indicating that the main reason for hydrogen embrittlement in this case was the reduction in the cohesion of grain boundaries, which could lead to the hydrogen assisted cracking without changing stress-strain behaviour of the steel, instead of hydrogen-dislocation interactions (Koyama, Akiyama, Tsuzaki & Raabe, 2013).…”
Section: Grain Boundariesmentioning
confidence: 99%
“…Since there are reports of significant degradation of mechanical properties of TWIP steels by hydrogen (Koyama et al, 2012b,c;Ryu et al, 2013), it is important to investigate the influence of hydrogen content on embrittlement behaviour on TWIP steels. In the study of Ryu et al (2013), the transformation of ɛ-martensite contributed to hydrogen embrittlement, and was attributed to the reduced SFE by hydrogen.…”
Section: Grain Boundariesmentioning
confidence: 99%